(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2023)
This article aims to vindicate the independence and impartiality of justice in Bolivia, within the framework of a constitutional legal system that tends to place the person and citizens as direct actors in the transformation of the current justice model, based on decisions adopted in Departmental Councils. The line of the study is condensed into “the approval of promoting and supporting the judicial reform via referendum”, through citizen legislative initiative. The democratic dynamics of this process that began (on 01-25-2023) will make visible whether the results of the reform proposal are effective in terms of independence and judicial coverage, compared to the model applied by the Plurinational Legislative Assembly (ALP), which bears a high-cost trust deficit for the Bolivian population, and of indigenous, original peasant community justice for more than fourteen years.